2007
DOI: 10.1128/jvi.00288-07
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Human Immunodeficiency Virus Type 1-Infected CD4+Cell Proteome: Dysregulated Cell Cycle Progression and Nuclear Transport Coincide with Robust Virus Production

Abstract: Relatively little is known at the functional genomic level about the global host response to human immunodeficiency virus type 1 (HIV-1) infection. Microarray analyses by several laboratories, including our own, have revealed that HIV-1 infection causes significant changes in host mRNA abundance and regulation of several cellular biological pathways. However, it remains unclear what consequences these changes bring about at the protein level. Here we report the expression levels of ϳ3,200 proteins in the CD4 ؉… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
87
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 95 publications
11
87
3
1
Order By: Relevance
“…The results presented here using both HIV-1-infected T cells and pNL4-3-transfected CD4  HeLa cells, along with the biochemical and physical evidence for virion-associated Nup62, Quantitative correspondence between this study and those of Chan et al (2007Chan et al ( , 2009). …”
Section: Hiv-1 Disperses Nups Into the Cytoplasm And Into Progeny Virusmentioning
confidence: 99%
“…The results presented here using both HIV-1-infected T cells and pNL4-3-transfected CD4  HeLa cells, along with the biochemical and physical evidence for virion-associated Nup62, Quantitative correspondence between this study and those of Chan et al (2007Chan et al ( , 2009). …”
Section: Hiv-1 Disperses Nups Into the Cytoplasm And Into Progeny Virusmentioning
confidence: 99%
“…Surface CD4 expression was verified in aliquots of isolated cells by flow cytometry on an FC500 flow cytometer (Beckman-Coulter) via fluorescein isothiocyanate (FITC)-conjugated anti-CD4 labeling (Miltenyi Biotec). HIV-1 LAI (3, 52) virus inoculum was prepared as described previously (6). Enriched CD4 ϩ…”
Section: Methodsmentioning
confidence: 99%
“…In the first proteomic analyses of HIV-1 infection in the CEMx174 cell line, we reported on protein abundance changes that correlated with G 1 /G 0 cell cycle arrest and alterations in Ran-mediated nuclear transport (6). A two-dimensional (2D) fluorescence difference gel electrophoresis analysis of HIV infection in the Jurkat cell line (42) also revealed changes in the protein abundance of host factors involved in nuclear transport, carbohydrate metabolism, and cell cycle progression in virus-producing CD4 cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis B virus, herpes simplex virus, influenza virus, and adenovirus also use NUPs for nuclear entry (Trotman et al 2001;König et al 2008König et al , 2010Copeland et al 2009;Schmitz et al 2010), whereas poliovirus and cardiovirus induce modifications of NUPs (Gustin and Sarnow 2001;Porter and Palmenberg 2009). Previous LC-MS/MS studies revealed that KTN1, NUP43, NUP358, NUP45, and NUP54 expression is downregulated on HIV-1 infection while NUP358, NUP98, and TPR expression is upregulated (Chan et al 2007; Monette et al 2011). …”
Section: Nucleoporins (Nups)mentioning
confidence: 99%